Recognizing the reagent microbiome - de Goffau, Marcus; Lager, Susanne; Salter, Susannah; Wagner, Josef; Kronbichler, Andreas; Jones, David Stephen; Peacock, Sharon J; Smith, GCS (Springer Nature, 2018)
A noticeable part of the microbiome literature, especially that working with low-biomass samples, is plagued by reagent contamination. Here we describe visual, statistical, methodical and ecological techniques to facilitate recognition of signals which represent contamination.
Keywords: DNA Contamination; Databases, Genetic; Gastrointestinal Microbiome; High-Throughput Nucleotide Sequencing; Humans; Indicators and Reagents; Microbiota; RNA, Ribosomal, 16S